Optimization of a hybrid highly elliptical orbit‐based navigation system for continuous high accuracy navigation: An optimum choice for regional navigation. Issue 2 (25th March 2019) - Malik, Rameez Ahmed; Jaffer, Ghulam; Hassan, Iqbal; Khan, Mohammad Yousaf
Abstract: A hybrid Highly elliptical orbit (HEO)‐based regional navigation system is optimized by examining the impact of variation of orbital parameters on navigation performance of the system. The principle of optimization is based on the following requirements: L and S band carrier frequency (user/receiver segment) link budget, satellite accessibility and dwell time over the area of interest, geometric configuration of the system, navigation accuracy, and constellation stability. The optimization algorithm is partnered with a dynamic simulation process. The optimal parameters (semi‐major axis, inclination, eccentricity, right ascension of ascending node, etc.) of the HEO‐based regional navigation system have been selected based on the results of the optimization process. The proposed hybrid system with four HEO and one geostationary earth orbit (GEO) satellite is a cost‐efficient and high‐accuracy navigation solution as compared with other regional systems.